Application of gamal Gliricidia sepium leaves compost as depuration agent of leads (Pb) in the body organ of red tilapia Oreochromis sp. - Robin; Nirmala, Kukuh; Harris, Enang; Affandi, Ridwan; Jusadi, Dedi (Indonesian Society of Scientific Aquaculture (ISSA), 2017)
ABSTRACT This study was aimed to perform depuration of Pb contained in tilapia body. The experiments were conducted in aquarium using compost of Gliricidia sepium leaf at a concentration of 10g/L, 20 g/L, 30 g/L, 40 g/L, and 0 g/L (control). The result showed that Pb level in fish muscle immersed with compost of Gliricidia leaf at a dose of 30 g/L for five days successfully decreased to a safe limit for human consumption (<0.3 mg/kg). However, decrease of Pb level in fish liver and kidney to finally reach the safe limit required seven days. Decreasing level of lead in the organs of experimental fish along with the increasing level of Pb in compost and maintenance media indicated that Pb accumulated in fish were released into the maintenance media by compost through chelation process. To conclude, compost of G. sepium leaves can be used as the material for depuration of Pb in the body of tilapia Keywords: humic acid, fulvic acid, depuration, Gliricidia leaves, lead, red tilapia ABSTRAK Penelitian ini bertujuan untuk mendepurasi Pb yang terkandung di tubuh ikan nila. Percobaan dilakukan di dalam akuarium menggunakan kompos daun gamal pada konsentrasi 10 g/L, 20 g/L, 30 g/L, 40 g/L, dan 0 g/L (kontrol). Hasil penelitian menunjukkan bahwa, Pb di daging ikan yang direndam dengan kompos daun gamal pada konsentrasi 30 g/L selama lima hari, kadarnya menurun hingga batas aman untuk dikonsumsi manusia (<0,3 mg/ kg). Penurunan Pb di hati dan ginjal untuk mencapai kadar aman membutuhkan waktu yang lebih lama, yakni tujuh hari. Seiring dengan menurunnya kadar Pb dalam organ ikan uji, kisaran Pb dalam kompos dan media budidaya meningkat, menunjukkan bahwa Pb dari tubuh ikan dilepaskan ke media budidaya dan terjadi proses khelat oleh kompos. Dengan demikian, kompos daun gamal bisa digunakan sebagai bahan pendepurasi Pb dari tubuh ikan nila. Kata kunci: asam humat, asam fulvik, depurasi, daun gamal, timbal, nila merah